Digital Citizenship Values In Algerian Second Generation Textbooks : A Content Analysis Of Third And Fourth Year Middle School Second Generation Textbooks Of Civic Education - عبد الهادي, امينة (University of Eloued جامعة الوادي, 2020)
While there are various types of teaching and learning materials, textbooks in print form have been crucial specific tools in the education process. These reliable resources are designed to meet the needs of a specific generation in a specific era. Today’s students’ needs; abilities and interactions are much different however. Given their interaction with digital technology and extensive use of social media sites, today’s’ students’ digital citizenship values are open to question. Central to this study are second generation civic education textbooks currently used in teaching third and fourth year middle school students and their critical role in enhancing the core digital citizenship values. Using mixed content analysis, the findings reveal the absence of the term ‘digital citizenship’ and the unsuccessful incorporation of the nine core digital citizenship concepts identified by Mike Ribble (2001). Ultimately, role and content of paper textbooks are to be up dated conveniently and therefore some ways to promote citizenship education of the digital environment adolescent learners grow up in are suggested.
مقال
Keywords: Paper textbooks ; Today's students ; Digital Era ; Digital natives ; Digital citizenship values